Investigating the Utilization of the Song 'Darl+ing' by Seventeen K-Pop Group in Improving English Grammar Skill - Riadil, Ikrar Genidal; Chonpracha, Pitchaya; Bujana, Novian Gilang; Nuswantoro, Aqila Gema (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2023)
Utilizing song as a medium for English language acquisition has emerged as a captivating and enjoyable approach incorporated within the curricula of Junior High School and Senior High School under the 2013 educational framework. This research aims to employ the song